Determinants of Economic Growth in Special Autonomous Regions: Does Capital Expenditure Important? - Afiska, Rizki Linda (E-Jurnal Akuntansi; Vol 34 No 11 (2024)DO - 10.24843/EJA.2024.v34.i11.p06, 2024)
This study aims to examine the influence of balancing funds, special autonomy funds, and regional own-source revenues on economic growth,  with  capital  expenditure  as  an  intervening  variable.  A purposive sampling method was used, selecting three Indonesian provinces:  Aceh,  Papua,  and  West  Papua.  Data  analysis  was conducted using panel data regression and path analysis models.The results indicate that balancing funds and regional own-source revenues do not significantly influence capital expenditure, whereas special autonomy funds have a significant positive effect on capital expenditure.  Additionally,  balancing  funds,  specialautonomy funds, and regional own-source revenues directly have a significant positive effect on economic growth, while capital expenditure does not  significantly  impact  economic  growth.  Path  analysis  further reveals that capital expenditure does not mediate the relationship between  balancing funds, special autonomy funds, regional own-source revenues, and economic growth.